Exposure to hypoglycemia and risk of stroke. Issue 1 (19th June 2018) - Smith, Logan; Chakraborty, Diya; Bhattacharya, Pallab; Sarmah, Deepaneeta; Koch, Sebastian; Dave, Kunjan R.
Abstract: In the treatment of both type 1 and type 2 diabetes mellitus, maintaining a euglycemic state represents one of the key challenges. Improper dosing and administration of glucose‐lowering drugs is associated with an increased risk of recurrent hypoglycemia episodes. In addition, the risk of adverse cardiovascular events in diabetic patients, particularly myocardial infarctions and strokes, is well established. Current research indicates a potential link between the baseline risk of cardio/cerebrovascular events in diabetic patients and exposure to hypoglycemia. In this review of the literature, we aim to determine if a relationship exists between recurrent hypoglycemia and adverse neurovascular events. Abstract : Chronic hyperglycemia in diabetic patients can lead to a variety of long‐term complications. Of particular importance is an increased risk of cardiovascular diseases, which is reported as the leading cause of death in diabetic patients. In this review of the literature, we aim to determine if a relationship exists between recurrent hypoglycemia and adverse neurovascular events.